Digitalisasi Marketing Melalui Instagram dan Facebook Ads dalam Meningkatkan Skala Usaha UMKM: Systematic Literature Review - Ulfa Afrianti; Mochammad Isa Anshori; Nurita Andriani (Universitas Muhammadiyah Surabaya, 2024)
The main problem in increasing the scale of MSME businesses is the digital platform that should be used in marketing programs. The purpose of this study is to answer the question of how the role of social media Instagram and Facebook Ads in increasing the scale of MSME businesses. This research applies the Systematic Literature Review method. The findings show that social media Instagram and Facebook Ads have contributed to the increase in business scale. Instagram and Facebook social media have played a role in increasing business scale and influencing consumer engagement and behavior, and generating data that supports marketing strategies.